Assessment of The Phenolic and Flavonoid Content in Certain Globe Artichoke (Cynara scolymus L.) Cultivars Grown in Northern Tunisia - Ilahy Riadh; Imen Tlili; Thouraya R'him; Zouhair Rached; kamel Arfaoui; Zoltàn Pék; Marcello Salvatore Lenucci; Hussein Daood; Lajos Helyes (Turkish Journal of Agriculture: Food Science and Technology)
Artichoke (Cynara scolymus L.) is a worldwide popular horticultural crop. Interest in assessing bioactive compounds with potential health benefits in artichoke is increasing. Therefore, in this study, the variability in total phenolic and flavonoid contents of six artichoke cultivars, including five purple namely Brindisie, Opal, Conserto, Romanesco and Rouge de France as well as an ordinary white artichoke variety were investigated. The results showed significant differences in total phenolic and flavonoid contents between artichoke cultivars. Total phenolic content ranged from 17.31 mg GAE/ g DW in the white artichoke variety to 21.31 mg GAE/g DW in Romanesco. Flavonoid content ranged from 4.51 mg RE/g DW in white artichoke to 7.06 mg RE/g DW in Rouge de France. Therefore, the highest total phenolic content was shown by Romanesco. However, the highest flavonoid content was recorded for both Opal and Rouge de France. This study demonstrates the importance of genotypic variability in shaping the levels of total phenolic and flavonoid, emphasizing the need to evaluate artichoke biodiversity in order to improve its nutritional value and to contribute towards increasing the intake of antioxidants.